2014
DOI: 10.1590/0001-3765201420130092
|View full text |Cite
|
Sign up to set email alerts
|

Low water quality in tropical fishponds in southeastern Brazil

Abstract: Expansion of aquaculture around the world has heavily impacted the environment. Because fertilizers are needed to raise fish, one of the main impacts is eutrophication, which lowers water quality and increases the frequency of algal blooms, mostly cyanobacteria. To evaluate whether the water quality in 30 fishponds in southeastern Brazilian met the requirements of Brazilian legislation, we analyzed biotic and abiotic water conditions. We expected that the high nutrient levels due to fertilization would cause l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 44 publications
0
9
0
1
Order By: Relevance
“…The turbidity values recommended by Conselho Nacional do Meio Ambiente (CONAMA-2005) are up to 100 NTU (around 69-81 mg L -1 depending on the type of sediment). Costa et al (2014) suggested that higher values are inappropriate for fish farming. Therefore, in general, water in Rio Grande do Sul is adequate for aquaculture based on turbidity, but fish farmers must avoid direct collection of water from rivers and lakes during periods of high turbidity, since the maximum values observed were up to 60 times the maximum recommended value.…”
Section: +mentioning
confidence: 99%
“…The turbidity values recommended by Conselho Nacional do Meio Ambiente (CONAMA-2005) are up to 100 NTU (around 69-81 mg L -1 depending on the type of sediment). Costa et al (2014) suggested that higher values are inappropriate for fish farming. Therefore, in general, water in Rio Grande do Sul is adequate for aquaculture based on turbidity, but fish farmers must avoid direct collection of water from rivers and lakes during periods of high turbidity, since the maximum values observed were up to 60 times the maximum recommended value.…”
Section: +mentioning
confidence: 99%
“…Planktonic algae are the primary producers of aquatic ecosystems and form the base of aquatic food webs that supports the zooplankton and fi sh (Graham et al, 2009;Rahman, 2015). Phytoplankton live in fl uctuating environment where many factors such as grazing pressure, sinking, light availability, nutrient uptake and nutrient turnover infl uence the distribution of phytoplankton in time and space (Crumpton and Wetzel, 1982;Costa et al, 2014). An important regulatory role in the control of the biomass and species composition of the algal assemblage is aff ected by their consumers, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Management of higher fi sh stock densities accompanied by higher nutrient loads result in increasing trophic status, ultimately reaching a state of hypertrophy in fi shponds. The main symptoms of this state across the world are the massive development of phytoplankton and cyanobacterial blooms, high fl uctuations in oxygen concentrations and pH, and high values of ammonia nitrogen destabilizing the fi shpond ecosystem (Komárková, 1998;Pechar, 2000;Potužák et al, 2007;Costa et al, 2014;Sipaúba-Tavares et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This promises employment and income-generating activities for locals and acts as a catalyst for social and economic development. Unfortunately, environmental impacts of fish aquaculture in reservoirs have been reported in many areas in Brazil, though these generally relate to eutrophication (Costa et al 2014).…”
Section: Introductionmentioning
confidence: 99%